Vegetation history and its links to climate change during the last 36 ka in arid Central Asia: Evidence from a loess-paleosol sequence in the Eastern Ili Valley - Liu, Peilun; Zhang, Shanjia; Qiu, Menghan; Ruan, Qiurong; Luo, Jiaming; Miao, Yunfa; Ling, Zhiyong (Frontiers in Earth Science, 2023)
Detailed vegetation history response to complex influencing factors of arid Central Asia (ACA) is crucial to understanding ecological sustainability. Here, we present the first pollen record in the Ili Valley during the Last Glacial Maximum (LGM) using the Jirentai (JRT) loess-paleosol sequence. Combining the results of multi-climate proxies and optically stimulated luminescence (OSL) dating, we aim to reconstruct the vegetative response to climate change since 36 ka B.P. Our results show that rapid loess accumulation in the JRT section began in the Late MIS3 (Marine isotope stage 3), and a thin paleosol layer developed in the Late LGM and Post Glacial. The pollen concentrations in the loess are significantly lower than in the paleosol, but the pollen assemblages are richer. Artemisia and Asteraceae are the dominant non-arboreal types in the loess, and abundant arboreal species are present (e.g., Pinus, Picea, Quercus, Betulaceae). The percentage of Artemisia remains high in the paleosol, and typical drought-tolerant plants are an important component (e.g., Amaranthaceae, Ephedra). We suggest that the species-rich arboreal pollen in the loess are transported by frequent and intense dust activities, which possibly originate from regional vegetation. Less diverse pollen assemblages in paleosol respond to the vegetation surrounding the JRT section. The vegetation history obtained from the JRT section shows that the lowlands of the Ili Valley were typical desert or desert-steppe vegetation for the past 36 ka. The surrounding mountains are dominated by Pinus and Picea forests. During the Early LGM, vegetation conditions deteriorated in both mountainous and lowland. The above phenomena coincide with the pollen records from lakes in the ACA. Our results further suggest that mountain forests reappear and the lowland environment improves in response to increased insolation in the Northern Hemisphere at high latitudes in the Late LGM. This point in time is earlier by about 5–10 ka compared to previous records. We attribute it to the fact that pollen assemblages from the loess-paleosol sequence are more sensitive to vegetation and climate change during the transition from the glacial to interglacial and propose a simple model to characterize them.